2020
DOI: 10.1021/acsami.9b21979
|View full text |Cite
|
Sign up to set email alerts
|

Armoring the Interface with Surfactants to Prevent the Adsorption of Monoclonal Antibodies

Abstract: The pharmaceutical industry uses surface-active agents (excipients) in protein drug formulations to prevent the aggregation, denaturation, and unwanted immunological response of therapeutic drugs in solution as well as at the air/water interface. However, the mechanism of adsorption, desorption, and aggregation of proteins at the interface in the presence of excipients remains poorly understood. The objective of this work is to explore the molecular-scale competitive adsorption process between surfactant-based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
53
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(65 citation statements)
references
References 71 publications
10
53
0
2
Order By: Relevance
“…44,45 Polysorbate suppresses protein adsorption by preferential location at the interface without forming complexes with the protein itself. 46,47 We could see similar effectiveness in protein adsorption reduction for PS80 and Poloxamer 188 (Fig. S4); the two surfactants were already shown to be effective in protein particle reduction in pumping studies.…”
Section: Discussionsupporting
confidence: 53%
“…44,45 Polysorbate suppresses protein adsorption by preferential location at the interface without forming complexes with the protein itself. 46,47 We could see similar effectiveness in protein adsorption reduction for PS80 and Poloxamer 188 (Fig. S4); the two surfactants were already shown to be effective in protein particle reduction in pumping studies.…”
Section: Discussionsupporting
confidence: 53%
“…The adsorption rate of the surfactant was even higher than that of the mAb, indicating the smaller PS20 molecules race to the tubing surface and coat it before mAb can adsorb. 68 These results are in line with our previous study where mAb adsorption was effectively reduced and particle formation during pumping substantially decreased in the presence of PS20. 7 The experiments with PS20 substantiate the hypothesis that mAb adsorption on silicone tubing is an interplay of an electrostatically dominated fast initial adsorption phase and hydrophobic interactions driving the final adsorption phase.…”
Section: Discussionsupporting
confidence: 92%
“…This same conclusion was reached in our earlier study of this mAb [Kanthe et al . ( 37 ) in which the mAb was referred to as mAb-1], which examined, using XRR, the competitive adsorption of a surfactant excipient to the air/water surface at an mAb concentration of 0.5 mg/ml and presented data for the protein adsorption alone at this single concentration. Given the fact that the surface concentrations for bulk concentrations in the range of 5 × 10 −2 to 1 mg/ml are close to the maximum packing values for side-on and end-on orientations, the preferred orientation cannot be conclusively determined.…”
Section: Resultsmentioning
confidence: 99%
“…However, these studies did not characterize the orientation of the adsorbed antibodies during the induction period or whether a change in orientation occurred during the condensation. The NR ( 31 , 38 , 39 ) and XRR ( 37 ) studies have measured adsorbed layer thicknesses and surface concentrations but did not examine in detail reorientation as the bulk concentration increased. Unfolding of IgGs adsorbed to an interface is not well understood: IRRAS studies ( 36 ) demonstrated minor unfolding of IgG structure, while the fluorescence studies ( 41 ) demonstrated an increase in surface hydrophobicity with adsorption possibly linked to protein unfolding.…”
Section: Introductionmentioning
confidence: 99%